Articulação entre pedagogia e as relações humanas: uma análise dos alunos quíchuas do Instituto Horacio Zevallos Gámez - Cusco - Huanca-Arohuanca, Jesús Wiliam (2021)
The results of the quantitative research process, whose objective was to analyze the articulation between pedagogy and human relations (HR) in the context of autonomy, environment, communication and comfort at the time of the development of the proposed themes, are presented. 70 students selected by means of an intentional sampling based on criteria, from the first semester of the Horacio Zevallos Gámez Higher Pedagogical Institute (HPI) of Cusco, in which the data were transferred and analyzed with the SPSS statistical program, participated. In conclusion, the existing problems lead to betting on alternative pedagogies to improve HR among those who teach and learn, as there are signs of discomfort, inconvenience and apathy of the interlocutors.